Rocket Media Development A Cardboard Waste Race to Improve the Cognitive Abilities of 4-5 Year Old Children in Kindergarten - Ismi Nurkhasanah; Yusuf, Muhammad; Isnaini Nur Azizah (Bulletin of Early Childhood, 2024)
The aim of this research is to develop innovative learning media made from cardboard waste, namely Rocket. Race, to improve the cognitive abilities of children aged 4–5 years in Qur'an Kindergarten Ma'arif Sumber Rejeki. The background of this research is based on the results of observations that show that most children are still in the "Beginning to Develop" or even "Not Yet Developed" category in cognitive aspects, especially indicators of counting, recognizing the concept of numbers, number symbols, and letters.This use Research and Development (R&D) method with 4D development model ( Define, Design, Develop, and Disseminate ).Subject study are 16 children selected ages 4–5 years​ with criteria child group A which has not reach optimal development in aspects cognitive.The research instruments included a cognitive development observation sheet and an expert validation questionnaire. Instrument validation was conducted through media and material expert tests, while data analysis was conducted quantitatively descriptively with a percentage of achievement. The results showed that the Rocket Race media was declared suitable for use based on media expert validation with an average score of 5 (very suitable category) and material expert validation with a score of 4–5 (suitable category). Limited trials showed that 90% of children were actively involved, 85% showed high enthusiasm, 80% experienced an increase in understanding of numbers, shapes, and colors, and 88% showed good social cooperation. Comparisons before and after media use also showed a significant increase from the categories of “Not Developing” (BB) and “Starting to Develop” (MB) to “Developing as Expected” (BSH). Teachers reported that this media was effective in making learning more interactive and enjoyable, while helping children focus on understanding basic concepts. Thus, the Rocket Race media is not only proven to be effective in improving children's cognitive abilities, but also encourages social skills, creativity, and provides environmental educational value through the use of recycled materials. This media is suitable for use as an alternative learning innovation that is environmentally friendly, cheap, and fun in PAUD.